The monastic genealogy of Hoḫʷärwa monastery – a unique witness of Betä Ǝsraʾel historiography - Dege-Müller, Sophia (Aethiopica, 2020)
During the course of a study of the manuscript tradition of the Betä Ǝsraʾel (Ethiopian Jews), the manuscript Jerusalem, National Library, Ms. Or. 87 came to light. This codex is a unique manuscript with several important elements that contribute to our knowledge of the history of the Betä Ǝsraʾel. Its by far most important feature are two short additional notes that I have come to call the Hoḫwärwa genealogy. This genealogy is the second piece of original pre-twentieth century Betä Ǝsraʾel historiography ever discovered, next to the text published by Leslau in 1946-47 as ‘A Falasha Religious Dispute.’ Taking the manuscript as a starting point, this article aims to cover topics such as the Betä Ǝsraʾel scribal tradition and aspects of their literature, their monasticism, the history of Hoḫwärwa monastery, and the history of the manuscript itself.